2020
DOI: 10.2196/15588
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Disadvantages of Electronic Patient-reported Outcome Measures: Systematic Review

Abstract: Background Patient-reported outcome measures (PROMs) are important in clinical practice and research. The growth of electronic health technologies provides unprecedented opportunities to systematically collect information via PROMs. Objective The aim of this study was to provide an objective and comprehensive overview of the benefits, barriers, and disadvantages of the digital collection of qualitative electronic patient-reported outcome measures (ePROM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
158
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 80 publications
(149 reference statements)
6
158
0
1
Order By: Relevance
“…The reference lists of all included studies were manually reviewed by KG and EP to identify articles missed in the database searches. In addition, the names of electronic symptom reporting systems discussed in previous reviews by Jensen et al (32), Warrington et al (33), and Meirte et al (25) were also searched in PubMed and Google Scholar to identify related studies meeting inclusion criteria that were not otherwise identified. For conference abstracts that met the inclusion criteria, the authors specifically looked for associated publications.…”
Section: Search Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…The reference lists of all included studies were manually reviewed by KG and EP to identify articles missed in the database searches. In addition, the names of electronic symptom reporting systems discussed in previous reviews by Jensen et al (32), Warrington et al (33), and Meirte et al (25) were also searched in PubMed and Google Scholar to identify related studies meeting inclusion criteria that were not otherwise identified. For conference abstracts that met the inclusion criteria, the authors specifically looked for associated publications.…”
Section: Search Strategymentioning
confidence: 99%
“…Self-report of systems through patient-reported outcome (PRO) instruments is now considered the gold standard for symptom assessment (21)(22)(23)(24). Indeed, a growing body of literature demonstrates that the use of PROs can enhance patient and clinician communication, inform health decision-making, and improve symptom management (25)(26)(27)(28)(29)(30)(31). For pragmatic and regulatory reasons, electronic systems provide the best method for collecting PROs (25).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations